Tailoring Adjuvant Endocrine Therapy for Premenopausal Breast Cancer - Francis, PA (2018)
Background: In the Suppression of Ovarian Function Trial (SOFT) and the Tamoxifen and Exemestane Trial (TEXT), the 5-year rates of recurrence of breast cancer were significantly lower among premenopausal women who received the aromatase inhibitor exemestane plus ovarian suppression than among those who received tamoxifen plus ovarian suppression. The addition of ovarian suppression to tamoxifen did not result in significantly lower recurrence rates than those with tamoxifen alone. Here, we report the updated results from the two trials. Methods: Premenopausal women were randomly assigned to receive 5 years of tamoxifen, tamoxifen plus ovarian suppression, or exemestane plus ovarian suppression in SOFT and to receive tamoxifen plus ovarian suppression or exemestane plus ovarian suppression in TEXT. Randomization was stratified according to the receipt of chemotherapy. Results: In SOFT, the 8-year disease-free survival rate was 78.9% with tamoxifen alone, 83.2% with tamoxifen plus ovarian suppression, and 85.9% with exemestane plus ovarian suppression (P=0.009 for tamoxifen alone vs. tamoxifen plus ovarian suppression). The 8-year rate of overall survival was 91.5% with tamoxifen alone, 93.3% with tamoxifen plus ovarian suppression, and 92.1% with exemestane plus ovarian suppression (P=0.01 for tamoxifen alone vs. tamoxifen plus ovarian suppression); among the women who remained premenopausal after chemotherapy, the rates were 85.1%, 89.4%, and 87.2%, respectively. Among the women with cancers that were negative for HER2 who received chemotherapy, the 8-year rate of distant recurrence with exemestane plus ovarian suppression was lower than the rate with tamoxifen plus ovarian suppression (by 7.0 percentage points in SOFT and by 5.0 percentage points in TEXT). Grade 3 or higher adverse events were reported in 24.6% of the tamoxifen-alone group, 31.0% of the tamoxifen-ovarian suppression group, and 32.3% of the exemestane-ovarian suppression group. Conclusions: Among premenopausal women with breast cancer, the addition of ovarian suppression to tamoxifen resulted in significantly higher 8-year rates of both disease-free and overall survival than tamoxifen alone. The use of exemestane plus ovarian suppression resulted in even higher rates of freedom from recurrence. The frequency of adverse events was higher in the two groups that received ovarian suppression than in the tamoxifen-alone group. (Funded by Pfizer and others; SOFT and TEXT ClinicalTrials.gov numbers, NCT00066690 and NCT00066703 , respectively.).